Physicochemical characteristics of beef meatballs fortified with edamame flour (Glycine max (L.) Merrill): Karakteristik fisikokimia bakso daging sapi dengan penambahan tepung edamame (Glycine max (L.) Merrill) - Nugroho, Wahid Yulianto; Hardianto, Yanuar Dandy; Rahayu, Premy Puspitawati (Jurnal Teknologi & Industri Hasil Pertanian, 2025)
Meatballs are a popular processed meat product made from minced meat combined with various additional ingredients, commonly including flour. Tapioca flour is often used, although it has relatively low nutritional content. Edamame flour, by contrast, offers enhanced nutritional value. The study aimed to determine the optimal percentage of edamame flour addition to improve the physicochemical properties of beef meatballs. The experimental method involved processing back leg beef meatballs with varying levels of edamame flour. A Completely Randomized Design (CRD) was used, consisting of four treatments and five replications: T0 (control), T1 (3% edamame flour), T2 (6% edamame flour), and T3 (9% edamame flour). The results revealed highly significant differences (P<0.01) in protein content and water-holding capacity (WHC), significant differences (P<0.05) in water content and texture, and no significant differences (P>0.05) in pH and fat content. The addition of 9% edamame flour (T3) yielded the best outcomes: pH (6.58), WHC (54.72%), texture (4.54 N), protein (16.32%), water content (67.42%), and fat content (8.14%). These results indicate improvements in the nutritional and physicochemical quality of beef meatballs. Therefore, edamame flour can be recommended as a functional ingredient to enhance meatball quality. The 9% level appears optimal for increasing protein and moisture retention, contributing to better texture and overall product quality. Future research should investigate sensory properties and consumer acceptance to support the potential for commercial application.